Weight evolution of beef cattle males intact or castrated at different ages - Restle, João; Grassi, Celso; Feijó, Gelson Luis Dias (Pesquisa Agropecuaria Brasileira, 1994)
Sixty-five crossbred Charolais x Zebu males were randomly distributed into the following treatments: T1. castration at 1,5 month of age; T2. castration at 8 months; T3. castration at 12 months and T4. intact males. Until weaning, at 8 months, the animals were kept on native pasture; afterward, until 12 months of age, they were kept on cultivated winter pasture. From 12 to 20 months they returned to native pasture and from 20 to 25 months they were kept on cultivated pasture. Age at castration did not affect animal weight gain (P > 0.05). Final live weight was higher (P < 0.05) for intact than for males castrated at younger (1.5 month) age; however, no difference was observed in relation to the males castrated at 8 or 12 months of age. From the total difference in weight gain between the intact and the castrated males, the largest one was obtained during the 20-25 month period. The results showed that the testicular hormones had more effect on the animal performance during the period of higher weight gain.